Age and Sex Differences in Balance Outcomes among Individuals with Chronic Obstructive Pulmonary Disease (COPD) at Risk of Falls. Issue 1 (31st December 2022) - Alsubheen, Sanaa A.; Beauchamp, Marla; Ellerton, Cindy; Goldstein, Roger; Alison, Jennifer; Dechman, Gail; Haines, Kimberley J.; Harrison, Samantha; Holland, Anne; Lee, Annemarie; Marques, Alda; Spencer, Lissa; et al.
Abstract: No previous research has examined age and sex differences in balance outcomes in individuals with chronic obstructive pulmonary disease (COPD) at risk of falls. A secondary analysis of baseline data from an ongoing trial of fall prevention in COPD was conducted. Age and sex differences were analyzed for the Berg Balance scale (BBS), Balance Evaluation System Test (BEST test) and Activities-specific Balance Confidence Scale (ABC). Overall, 223 individuals with COPD were included. Females had higher balance impairments than males [BBS: mean (SD) = 47 (8) vs. 49 (6) points; BEST test: 73 (16) vs. 80 (16) points], and a lower confidence to perform functional activities [ABC = 66 (21) vs. 77 (19)]. Compared to a younger age (50–65 years) group, age >65 years was moderately associated with poor balance control [BBS ( r  = − 0.37), BEST test ( r  = − 0.33)] and weakly with the ABC scale ( r  = − 0.13). After controlling for the effect of balance risk factors, age, baseline dyspnea index (BDI), and the 6-min walk test (6-MWT) explained 38% of the variability in the BBS; age, sex, BDI, and 6-MWT explained 40% of the variability in the BEST test; And BDI and the 6-MWT explained 44% of the variability in the ABC scale. This study highlights age and sex differences in balance outcomes among individuals with COPD at risk of falls. Recognition of these differences has implications for pulmonary rehabilitation and fall prevention in COPD, particularly among females and older adults.